2013
DOI: 10.1073/pnas.1222798110
|View full text |Cite
|
Sign up to set email alerts
|

Essential requirement for IRF8 and SLC15A4 implicates plasmacytoid dendritic cells in the pathogenesis of lupus

Abstract: In vitro evidence suggests that plasmacytoid dendritic cells (pDCs) are intimately involved in the pathogenesis of lupus. However, it remains to be determined whether these cells are required in vivo for disease development, and whether their contribution is restricted to hyperproduction of type I IFNs. To address these issues, we created lupus-predisposed mice lacking the IFN regulatory factor 8 (IRF8) or carrying a mutation that impairs the peptide/histidine transporter solute carrier family 15, member 4 (SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
123
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 67 publications
13
123
1
Order By: Relevance
“…Moreover, IFN-α signaling promotes autoimmune (1), viral (2)(3)(4)(5), and bacterial disease pathogenesis (6). Suppression of IFN-α signaling has demonstrated efficacy in multiple autoimmune mouse models (7)(8)(9) and during influenza viral infection (4,10); however, the mechanism by which sphingosine 1-phosphate receptor 1 (S1PR1) signaling prevents IFN-α amplification during these disease states is currently unknown.…”
mentioning
confidence: 99%
“…Moreover, IFN-α signaling promotes autoimmune (1), viral (2)(3)(4)(5), and bacterial disease pathogenesis (6). Suppression of IFN-α signaling has demonstrated efficacy in multiple autoimmune mouse models (7)(8)(9) and during influenza viral infection (4,10); however, the mechanism by which sphingosine 1-phosphate receptor 1 (S1PR1) signaling prevents IFN-α amplification during these disease states is currently unknown.…”
mentioning
confidence: 99%
“…Conversely, pDCs express TLR-7 and abundant type 1 interferons but lack the ability to present antigen in noninflammatory conditions (7,8). pDCs have been implicated in the pathogenesis of systemic lupus erythematosus (9,10), whereas cDCs are critical for activating killer T cells (CTLs) against Listeria and Plasmodia (1) and immune responses to proteinaceous vaccines (2). The DC subsets have different lifespans (11,12).…”
mentioning
confidence: 99%
“…IRF8 is highly expressed in mouse and human GCs (15,30) and shares a large number of common target genes in GC B cells, about half of which are also targeted by PU.1 (16). IRF8 has also been implicated in the development of B cell-driven systemic autoimmune diseases in humans and mice (31,32). Finally, several recent studies have identified roles for IRF8 in the pathogenesis of human diffuse large B cell lymphoma (33,34) and probably mouse diffuse large B cell lymphoma as well (15).…”
Section: Discussionmentioning
confidence: 99%